RISK-ORIENTED THINKING IN THE QUALITY MANAGEMENT SYSTEM OF AN ORGANIZATION - Andreevna Katanaeva, Marina; Ilyich Grozovsky, Gennady; Aleksandrovna Lartseva, Tatyana; Fedorovna Vyacheslavova, Olga; EvgenievnaParfenyeva, Irina (Revista Inclusiones, 2019)
High dynamics of modern production development lead to many new tasks and, at the same time, an increased level of risk and its diversity. This makes enterprises not only periodically, but constantly identify new risks, analyze them and develop appropriate methods for their management based on risk-oriented thinking, the basic principles of which are formulated in ISO 31000 and ISO 9001. The article presents risk-oriented thinking models in quality management system and risk management in quality management system, allowing one to carry out management activities in a situation of uncertainty and make decisions aimed at preventing mistakes in the management of organization and ensuring proper quality.